Konsep Perancangan Adaptif pada GOR Saparua Bandung: Dialog antara Preservasi Nilai Sejarah, Kebutuhan Moderen dan Fungsional - Manda, Christianto Cornelius Raja; Herwindo, Rahadhian Prajudi (Arsir: Jurnal Arsitektur, 2026)
Saparua Sports Hall in Bandung, a type C cultural heritage building designed in the Jengki architectural style, faces a challenge between the preservation of its historical value and the demands of moderen functionality. The building possesses significant historical and architectural merit, particularly its wooden façade, yet its spatial layout and facilities no longer meet contemporary standards. This research aims to formulate an adaptive design concept that bridges these two aspects through a qualitative approach and a case study. The result is a concept centered on a "dialogue" between old and new elements. This includes the restoration of the wood and natural stone façade, a flexible reorganization of the internal space, and the addition of lightweight moderen elements that do not dominate the original character of the building. This strategy facilitates a harmonious functional adaptation, transforming Saparua Sports Hall from merely a historical monument into a relevant sporting venue for the moderen era. This study underscores the importance of balancing cultural value preservation with practical needs, noting that limited documentation presents a primary challenge. The proposed concept can serve as a reference for the revitalization of similar cultural heritage buildings.